Persistence of immunoglobulin-producing cells in parotid salivary glands of patients with primary Sjögren's syndrome after B cell depletion therapy. Issue 11 (21st May 2012) - Hamza, Nishath; Bootsma, Hendrika; Yuvaraj, Saravanan; Spijkervet, Fred K L; Haacke, Erlin A; Pollard, Rodney P E; Visser, Annie; Vissink, Arjan; Kallenberg, Cees G M; Kroese, Frans G M; Bos, Nicolaas A
Abstract : Objectives: To assess the persistence of immunoglobulin-producing cell populations in the parotid salivary glands of patients with primary Sjögren's syndrome (pSS) after B cell depletion therapy with rituximab. Methods: Thirteen patients with pSS and four control patients were included in this study. Patients with pSS were treated with rituximab or placebo. Sequence analysis was carried out on IgA- and IgG-encoding transcripts extracted from parotid salivary gland biopsy specimens taken before treatment and at 12–16 and 36–52 weeks after treatment. Results: At baseline, many clonally related sequences were seen in patients with pSS. The number of clonal expansions was significantly higher in patients with pSS than in control patients. Clonal expansions were composed of IgA- and/or IgG-expressing cells. Rituximab did not significantly alter the degree of clonal expansions. Groups of clonally related cells had members which were shared between biopsy specimens taken before and after treatment. Mutation frequencies of immunoglobulin sequences from clonally related cells in patients with pSS were higher after treatment. Conclusions: Rituximab treatment does not alter the characteristic features of increased clonal expansions seen in the parotid salivary glands of patients with pSS. The presence of clonally related immunoglobulin-producing cells before and after rituximab treatment strongly suggests that immunoglobulin-producing cells persist in salivary glands of patients with pSS despite B cell depletion. The presence of mixed isotype expression within groups of clonally related cells indicates local class switching in salivary glands of patients with pSS. Persistent immunoglobulin-producing cells may underlie disease relapse after treatment.